Prevalence of hemoglobinopathies in different regions and castes of Uttar Pradesh, India -A hospital based study - Verma, Pratima; Ghildiyal, Archna; Verma, Dileep; Krishna, Akhilesh; Singh, Shraddha; Kumar, Ashutosh; Tiwari, Sunita (Asian Journal of Medical Sciences, 2015)
Background: Thalasemia and other hemoglobinopathies are found in all the states of India and their prevalence is quite variable. In Uttar Pradesh very few studies are found which explore the spectrum of hemoglobinopathies. There is no such study which identifies the geographic distribution of high-risk communities with frequencies of hemoglobinopathies. Aim: Present study was carried out to determine the prevalence of hemoglobinopathies in different regions and castes of Uttar-Pradesh (UP) state. Materials and Methods: This is a preliminary community based cross-sectional, hospital based study, conducted at King George’s Medical University, Lucknow, Uttar- Pradesh. Subjects aged between 18 to 65 years were enrolled for sampling. The anticoagulated blood was used for performing CBC (complete blood count), and hemoglobin electrophoresis to measure hemoglobinopathies. Results: The present study revealed higher(28/194;19.5%,p